Rancang Bangun Alat Pendeteksi Ketinggian Permukaan Air Berbasis Mikrokontroler Arduino Uno - Yakob, Muhammad; Sagita, Nila; Putra, Rachmad Almi (JURUTERA - Jurnal Umum Teknik Terapan, 2019)
Automatic monitoring of changes in water level by applying microcontroller technology as a data processing media and HC-SR04 Ultrasonic Sensor as distance reading media produces output in the form of information on changes in water level where the tool will also activate the Buzzer as an early warning marker for the surrounding community that signifies change water level This tool can reduce physical losses and fatalities due to changes in water level. Making Water Surface Height Detection Tool Using Arduino Uno Microcontroller consists of several stages, namely making block diagrams, designing a system consisting of hardware, software, and program design, testing tools, tool calibration and data retrieval. Based on the results of the tests that have been carried out the results show that the Water Surface Height Detection Tool works as expected.